Harmoni Beragama Melalui Pendidikan Multikultural dalam Studi Pendidikan Agama Islam di Indonesia-Singapura - Erawati, Dyah; Djabarudin, Maryam; Nuranisa, Vina (Addabani: Interdisciplinary Journal of Islamic Education, 2026)
This study examines the comparative philosophy of multicultural education in the context of Islamic Religious Education (PAI) in Indonesia and Singapore. Amidst increasingly complex societal diversity, understanding and implementing multicultural education are crucial, particularly in shaping students' character as tolerant and inclusive. The background to this research problem is the need to examine how the two countries, with different social and cultural contexts, integrate the principles of multicultural education into Islamic Religious Education. The main objective of this study is to analyze and compare the philosophical foundations of multicultural education underlying Islamic Religious Education in Indonesia and Singapore, and to identify similarities and differences. The research method is a qualitative comparative study using content analysis of educational policy documents, Islamic Religious Education curricula, and relevant academic literature from both countries. The results show that Indonesia, with its Pancasila philosophy, tends to prioritize inclusivity and tolerance in Islamic Religious Education, reflecting internal diversity. Meanwhile, Singapore emphasizes social cohesion and national identity through multicultural education integrated into general religious subjects. While they differ in philosophical emphases, both share the common goal of creating a harmonious society. This research recommends strengthening intercultural philosophical dialogue in the development of Islamic Religious Education (PAI) curricula in both countries to promote a deeper understanding of universal human values.